Effect of Geobacillus toebii GT-02 addition on composition transformations and microbial community during thermophilic fermentation of bean dregs - Xiaojia Chen (Nature Portfolio, 2021)
Abstract Bean dregs can be prepared into organic fertilizer by microbial fermentation. Geobacillus toebii GT-02, which has promoting effect on bean dregs fermentation, was isolated from horse dung and it grows within a range of 40–75 °C and pH 6.50–9.50. The effectiveness of GT-02 addition on composition transformations and the microbial community in bean dregs thermophilic fermentation at 70 °C for 5 days was investigated (T1). Fermentation of bean dregs without GT-02 served as control (CK). The results showed that T1 (the germination index (GI) = 95.06%) and CK (GI = 86.42%) reached maturity (defined by GI ≥ 85%) on day 3 and day 5, respectively. In addition, the total nitrogen loss of T1 (18.46%) on day 3 was lower than that in CK (24.12%). After thermophilic fermentation, the total organic carbon and dry matter loss of T1 (53.51% and 54.16%) was higher than that in CK (41.72% and 42.82%). The mean microbial number in T1 was 4.94 × 107 CFUs/g dry matter, which was 5.37 times higher than that in CK. 16S rDNA sequencing identified Bacillus, Geobacillus and Thermobacillus as dominant in CK, while Bacillus, Ammoniibacillus and Geobacillus were dominant in T1. A canonical correspondence analysis showed that Geobacillus and Ammoniibacillus were positively correlated with the GI. Thus, thermophilic fermentation with GT-02 can promote the maturity of bean dregs, which indicated the potential application value of GT-02 in thermophilic fermentation.